Comparison of the conventional frozen elephant trunk implantation technique with a modified implantation technique in zone 1. (29th August 2019) - Gottardi, Roman; Voetsch, Andreas; Krombholz-Reindl, Philip; Winkler, Andreas; Steindl, Johannes; Dinges, Christian; Kirnbauer, Michael; Neuner, Matthias; Berger, Tim; Seitelberger, Rainald
Abstract: : OBJECTIVES: The aim of the study was to compare the conventional frozen elephant trunk implantation technique with a modified implantation technique with an aortic anastomosis in zone 1 and extra-anatomic revascularization of the left subclavian artery during reperfusion. METHODS: Between May 2014 and March 2018, 40 patients (26 male; mean age 60.2 ± 11.2 years) underwent complete aortic arch replacement with the Thoraflex Hybrid prosthesis™ (Vascutek, Inchinnan, Scotland) at our institution. Seventeen patients underwent conventional arch replacement (group 1) and 23 patients the modified procedure (group 2). Indication for arch replacement included all types of acute and chronic diseases. RESULTS: Cardiopulmonary bypass time (213.1 ± 53.5 vs 243.8 ± 67.0 min, P  = 0.13) and aortic cross-clamp time (114.4 ± 40.7 vs 117.3 ± 56.6 min, P  = 0.86) did not differ significantly between group 1 and 2. There was a trend towards a shorter circulatory arrest time (50.72 ± 9.6 vs 44.7 ± 15.5 min; P  = 0.20) in group 2. Perioperative mortality was 10% (5.9% vs 13%; P  = 0.62). Stroke occurred in 10% (5.9% vs 13%; P  = 0.62) of patients. Spinal cord injury occurred in 7.5% of patients (11.8% vs 4.3% P  = 0.57). Due to the a proximal aortic anastomosis, there was a significantly shorter coverage of the descending aorta with the prosthesis ending at vertebral level Th7.5 (6.75–8) in group 1 versus Th6.0 (5.0–6.0) in group 2 ( P -value = 0.004). CONCLUSIONS: Implantation of the frozen elephant trunk prosthesis in zone 1 allows for a more proximal aortic anastomosis that could make the procedure more feasible especially in patients with difficult anatomies or in an acute setting.